Computation of Maximum Permissible Bank Finance For Working Capital: A study on liquidity management in Indian banking (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Current assets are generated along the pipeline ofproductive-distributive system of the enterprise. These gross current assets (GCA) capture fund, or in other words, theyneed financing. The first source of the financing is creditors. When creditorsare deducted from GCA, what is left is purely called working capital gap (WCG) in Indian banking parlance. Funding ofthis gap comes from three sources viz. Bank Finance (BF), Short-term Finance(SF) and the long term fund of enterprises, known as margin or net workingcapital (NWC). In India, banks would not like NWC to become zero ornegative. They insist that the current ratio, which is an expression of NWClevel of the enterprise, be positive. The banker views even a slip back incurrent ratio unfavorably. This ratio, which was invented by the bankers as faras back as 1890, continues to occupy the percentage in the credit appraisalsystem of any commercial bank in India. Liquidity of any businesses enterpriseis still determined by current ratio, though notion of liquidity hassubstantial change in modern day financial management. Current assets areconsidered in the decreasing order of their liquidity or stability. Quickratio, which is the more refined form of the current ratio, is calculated onthe first three current assets, which according to ruling notion provide mostliquidity to a business1. Inventories are considered to be the liquid amongthem. The above concept of the liquidity is found to be narrow, because it doesnot take into consideration total operations of the business. Generallyspeaking, the purpose of liquidity is to ensure smooth operation of thebusiness.